A tectonic carpet of Variscan flysch at the base of a rootless accretionary prism in northwestern Iberia: U–Pb zircon age constrains from sediments and volcanic olistoliths - Clavijo, Emilio (2022)
The allochthonous complexes of Galicia–Trás-os-Montes Zone (NW Iberia) are part of a rootless tectonic stack which preserves part of a Variscan accretionary prism. They are formed by individual tectonic slices marked by specific tectonometamorphic evolutions, which were piled up in a piggy-back mode onto its relative autochthon, the Central Iberian Zone (CIZ). Allochthony decreases from the structurally upper thrust sheets towards the lower ones. The lowermost unit of the stack is known as the Parautochthon or Schistose Domain. It is characterized by a low metamorphic grade in contrast with higher temperatures and/or pressures estimated for the overlying allochthonous units and shares the stratigraphic sequence with the underlying autochthon. The Parautochthon is divided in two structural and stratigraphic sub-units: (i) the Lower Parautochthon (LPa) is made of synorogenic flysch-type sediments with varied turbiditic units and olistostrome bodies, showing Upper Devonian–lower Carboniferous age according to the youngest zircon populations and fossiliferous content; (ii) the Upper Parautochthon (UPa) is composed of highly deformed preorogenic upper Cambrian–Silurian volcano-sedimentary sequence comparable with the nearby autochthon and to some extent, also with the high-P and low-T Lower Allochthon laying structurally above. The UPa was emplaced onto the LPa along the Main-Trás-os-Montes Thrust, and the LPa became detached from the CIZ relative autochthon by a regional-scale structure, the Basal Lower Parautochthon Detachment, which follows a weak horizon of Silurian carbonaceous slates. A review on the detrital zircon studies on the synorogenic LPa complemented by zircon dating of 17 new samples is presented here. The results support the extension of the LPa underneath the NW Iberian allochthonous complexes, from Cabo Ortegal, to Bragança and Morais massifs. Its current exposure follows the lowermost tectonic boundary between the Galicia–Trás-os-Montes (allochthon) and Central Iberian (autochthon) zones. The youngest zircon age populations point to a maximum sedimentation age for the LPa formations ranging from Famennian to Serpukhovian and supports the piggy-back mode of emplacement of the Galicia–Trás-os-Montes Zone, of which it represents the latest imbricate. The zircon age populations in the LPa allow the sedimentary provenance areas to be constrained, showing the intervention of nearby sources (mostly the UPa) and/or multiply recycled and long-transport sediments with a typically north-central Gondwana age fingerprint, also found in the Lower Allochthon, UPa and Autochthon. Complementary geochronology of volcanic olistoliths trapped in the LPa sediments and of late Cambrian to Upper Ordovician rhyolites from the UPa is also presented. It shows a direct relationship between the major blocks source area (UPa) and the setting place (LPa). Old zircon age patterns show that the LPa sedimentary rocks were recycled from detrital rocks of the allochthon (advancing wedge) and the nearby autochthon (peripheral bulge).